Akame ga kill! 8 - Takahiro, 1981- (Takahiro, 1981- Akame ga kiru!, 2016)
"Akame and her teammates have finally arrived at the headquarters of the religious organization but awaiting them are both the Jaegers and the Four Demons from the Temple of the Imperial Fist! And in the midst of the most intense battle yet, Mine finally gets her chance to confront Seryu!!"--Back cover.